La importancia del Derecho Civil y de su codificación en la sociedad. Entrevista a Fernando Vidal Ramírez - Pérez Caruajulca, Miguel Ángel; Vidal Ramírez, Fernando (Pontificia Universidad Católica del Perú, 2014)
Civil Law is still one of the most important areas of the legal field. Its consideration as the Common Law is still dormant.In this sense, Professor Fernando Vidal Ramirez talks about the birth, evolution and importance of Civil Law in the society, explaining the role played by civil codification. Finally, he talks about his experience as a member of the Reformer Commission of the 1936 Civil Code, which allowed the provision of the still in force Peruvian Civil Code of 1984.

El Derecho Civil continúa siendo una de las áreas más importantes del ámbito jurídico. Su consideración como el Derecho Común sigueaún latente.En ese sentido, el profesor Fernando Vidal Ra- mírez habla sobre el nacimiento, evolución e importancia del Derecho Civil en la sociedad, explicando el rol que cumple la codificación civil. Finalmente, cuenta su experiencia como miembro de la Comisión Reformadora del Código Civil de 1936, la cual permitió la dación del todavía vigente Código Civil de 1984.
The importance of Civil Law and codification for society. Interview to Fernando Vidal Ramírez
Keywords: Law; Civil Law; Civil Code; Civil Codification; Roman Law; Civil Code Reform; Derecho civil; Código civil; Codificación civil; Derecho romano; Reforma del código civil; https://purl.org/pe-repo/ocde/ford#5.05.01